Influence of solvent additive on the performance and aging behavior of non-fullerene organic solar cells. (15th January 2022) - Arredondo, Belén; Carlos Pérez-Martínez, José; Muñoz-Díaz, Laura; López-González, Maria del Carmen; Martín-Martín, Diego; del Pozo, Gonzalo; Hernández-Balaguera, Enrique; Romero, Beatriz; Lamminaho, Jani; Turkovic, Vida; Madsen, Morten
Graphical abstract: Highlights: The incorporation of DIO to the solvent of the active layer PBDB-T:ITIC improves morphology, increases mobility and enhances device efficiency in pristine state. The incorporation of DIO reduces the initial burn-in effect, but enhances degradation at longer time scales. During degradation, DIO cells show an increase of series resistance that dramatically affects FF. Physical simulations confirm that the quasi-Fermi level for holes pins at the HTL interface when the anode WF is 5 eV or below, removing the VOC dependence on light intensity. Abstract: The performance of organic solar cells has improved significantly in recent years due to the use of non-fullerene acceptors (NFA). While processing additives are typically added to the active layer blends to enhance device performance in NFA organic solar cells, their impact on device degradation remains unclear. In this work we have compared the performance, in pristine and degraded state, between air-processed slot-die coated NFA ITO-free organic solar cells with and without the processing additive DIO, using a structure of PET/Ag/ZnO/PBDB-T:ITIC/FHC PEDOT:PSS. We observed an improvement in the power conversion efficiency of the devices when adding DIO, from 4.03% up to 4.97%. The evolution of the performance for both devices under ISOS-L1 life testing protocol reveals that the drop in efficiency is mainly due to a decay of JSC for both cells. In the short time scale the efficiency of non-DIO cells decays faster than the DIO cells, whereas in the long time scale the efficiency of non-DIO cells tends to stabilize sooner. Carrier mobilities estimated from impedance measurements decrease with time at similar rate for both degraded samples. Besides, DIO devices present a steep increase of the series resistance with time causing a decrease of the FF and thus of the efficiency. Moreover, in both degraded devices, the open-circuit voltage saturates with increasing illumination intensity. Numerical simulations reveal that a reduced anode work function of 5 eV is needed to fit experimental data.